Moebius Syndrome: Clinical Manifestations in a Pediatric Patient - Lima, Luciana Monti [UNESP]; Diniz, Michele Baffi [UNESP]; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP] (Amer Acad Pediatric Dentistry, 2009)
Moebius syndrome is a congenital, nonprogressive disorder clinically characterized by loss of facial expression, impaired stomatognathic system functions, incapacity to close the eyelids, and several oral impairments. The purpose of this paper was to present the clinical manifestations and the dental treatment in a 5-year, 2-month-old male Moebius syndrome patient. The child presented with facial asymmetry, difficulty performing facial mimic movements and pronouncing some letters, and compromised suction, mastication, breathing, and deglutition. An intraoral examination revealed hypofunction of the perioral muscles, cheeks and tongue, ankyloglossia, anterior open bite, and absence of carious lesions and dental anomalies. The dental treatment consisted of frenectomy and further placement of a removable orthodontic appliance with a palatal crib for correction of the anterior open bite. After 12 months of follow-up, anterior open bite decreased and speech, deglutition, and mastication improved. (Pediatr Dent 2009;31:289-93) Received March 8, 2008 vertical bar Lost Revision July 22, 2008 vertical bar Revision Accepted July 28, 2008
Keywords: MOEBIUS SYNDROME; ORAL FINDINGS; ETIOLOGY; CHILD